If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 39(x + 2) = 63x Reorder the terms: 39(2 + x) = 63x (2 * 39 + x * 39) = 63x (78 + 39x) = 63x Solving 78 + 39x = 63x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-63x' to each side of the equation. 78 + 39x + -63x = 63x + -63x Combine like terms: 39x + -63x = -24x 78 + -24x = 63x + -63x Combine like terms: 63x + -63x = 0 78 + -24x = 0 Add '-78' to each side of the equation. 78 + -78 + -24x = 0 + -78 Combine like terms: 78 + -78 = 0 0 + -24x = 0 + -78 -24x = 0 + -78 Combine like terms: 0 + -78 = -78 -24x = -78 Divide each side by '-24'. x = 3.25 Simplifying x = 3.25
| -8x^6-16x^5+64x^4=0 | | (9+7)-7=-8(x+2) | | -4.9x^2+7.6x+25=0 | | (3x-7)-(x-4)=0 | | 4(x-4)+x=5(x-5)+9 | | 9=p+15 | | (4+u)(5u-8)=0 | | -3x^6-9x^5+120x^4=0 | | 7x^2-11x-26=0 | | 11(x-4)=121 | | a^2-16ax+60x^2=0 | | s^2+11sd+28d^2=0 | | 47-T=T-6 | | (x)(x)-25=0 | | 47+(t-6)=T | | q=4.7 | | -4(n-2)=2-3n | | 6x+90-x=180 | | 4(-2+1.25y)+6=5y-2 | | 8x+5=4x+3 | | 15=7a+3-1a | | 47q=47+q | | (5)y*y-y-4=0 | | 2(x+8)+7=2x+5 | | 3y-12=(-2y)+(-12) | | 24x-15= | | 3y-12=-2y+(-12) | | 1.5x^2+60x-190=0 | | (3)t*t-7t-20=0 | | 832=(x+10-4)(x-4)(2) | | -2y(3+4)=5x+2 | | 4x+6=5y-2 |